2014
DOI: 10.1186/1749-8090-9-17
|View full text |Cite
|
Sign up to set email alerts
|

Seventeen-millimeter St. Jude Medical Regent valve in patients with small aortic annulus: dose moderate prosthesis-patient mismatch matter?

Abstract: BackgroundThe study was designed to evaluate the effects of moderate prosthesis-patient mismatch (defined as 0.65 cm2/m2 < indexed effective orifice area ≤ 0.85 cm2/m2) on midterm outcomes after isolated aortic valve replacement with a 17-mm St. Jude Medical Regent valve in a large series of patients, and to determine if these effects are influenced by patient confounding variables.MethodsOne-hundred and six patients with and without moderate prosthesis-patient mismatch early after implantation of a 17-mm Rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…24 In Asia, maintaining PT-INR at such lower levels is accepted in some institutions. 5,29 Considering differences among races, Takaseya and colleagues 4 reported that the target INR level should be higher in Caucasian than Asian patients because of differences between them in the pharmacodynamics of warfarin. Other reports recommend close monitoring of PT-INR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 In Asia, maintaining PT-INR at such lower levels is accepted in some institutions. 5,29 Considering differences among races, Takaseya and colleagues 4 reported that the target INR level should be higher in Caucasian than Asian patients because of differences between them in the pharmacodynamics of warfarin. Other reports recommend close monitoring of PT-INR.…”
Section: Discussionmentioning
confidence: 99%
“…With this type of small valve, PPM should be considered. To prevent PPM, 29,30 effective orifice area index at rest ideally should not be less than 0.85 cm 2 /m 2 . However, this goal must be evaluated in light of the anticipated risks and benefits for a given patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hydrodynamic in vitro model study conducted by Bottio et al [ 10 ], compared 5 different bi-leaflet mechanical valves in the small annulus and concluded that the hydrodynamic superiority with St. Jude regent flexicuff and sorin bicarbon valve (Sorin Biomedica, Saluggia, Italy). A small-sized bi-leaflet mechanical valve with better EOA provides better outcomes [ 7 9 , 11 , 12 ] and is also comparable with that of ARE [ 4 ]. Despite having the risk of PPM, it has several advantages including shorter CPB time, simpler technique, and reduced incidence of bleeding and infection.…”
Section: Discussionmentioning
confidence: 99%
“…Standard M-mode and Doppler measurements were obtained according to the American Society of Echocardiography criteria. M mode measurements were based on the mean of three measures on two different cardiac cycles, while Doppler measurements were the mean of more than three and five cycles in the case of sinus rhythm and atrial fibrillation, respectively [ 7 ]. The following variables were taken: left ventricular ejection fraction (LVEF) and right ventricular function, MPG, PPG across the valves, and wall dimensions, pulmonary artery systolic pressure (PASP).…”
Section: Methodsmentioning
confidence: 99%